Representing capital in cinema - Guichet, Tomás (2020)
The work is about the analysis of the representation of capital in cinema. There were analyzed different attempts to present it and clarified the main ideas of Karl Marx. The history of capitalism criticism in cinema; the book Representing Capital from Jameson; Toskano & Jeff Kinkle´s book Cartographies of the Absolute, Sergei Eisenstein´s attempt to film the book The Capital and Alexander Kluge´s movie News from the ideological antiquity to find my own way of presenting the capital. The second chapter is the film report of the final movie O Tapete which shows my way to criticize the capital system and concludes the third part of the thesis.